The cognitive neuroscience of religious experience decentering and the self - McNamara, Patrick 1956- (Cambridge University Press, 2022)
The Cognitive Neuroscience of Religious Experience, now updated and expanded in a new edition, updates key topics covered in the first edition including: decentering and self-transformation, supernatural agent cognitions, mystical states, religious language, ritualization, and religious group agency. It expands upon the first edition to include major findings on brain and religious experience over the past decade, focusing on methodology, future thinking, and psychedelics. It provides an up-to-date review of brain-based accounts of religious experiences, and systematically examines the rationale for utilizing neuroscience approaches to religion. While it is primarily intended for religious studies scholars, people interested in comparative religion, philosophy of religion, cultural evolution, and personal self-transformation will find an account of how such transformation is accomplished within religious contexts
Title from publisher's bibliographic system (viewed on 09 Jun 2022)
Keywords: Psychology, Religious; Evolutionary psychology